Analisis Tingkat Ketergantungan Fiskal dan Hubungannya dengan Pertumbuhan Ekonomi Kota Jambi - Wijaya, Dito; Haryadi, Haryadi; Zulgani, Zulgani (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2015)
This study aimed to quantify the fiscal needs in the city jambi and analyze the relationship between the level of fiscal dependency of between the level of fiscal dependency of economic growth in the city of Jambi and see how big the city’s fiscal dependence on the central govermeny Jambi. The results of this study indicate that the Fiscal Needs  in Jambi has increased significantly each  year,  with an  average growth of 27  times  greater where the level of dependence of the Local Government Fiscal Jambi city against the central government is still very High, on average within 6 year (2008 to 2013) obtained the proportion of revenue to the level of fiscal decentralization Jambi each including a small category with an average of 10.93%. This suggests that the fiscal capacity of the city of Jambi to implement regional autonomy  means  that  the  dependency  ratio  is  the  small  city  of  Jambi  to  the  central government is very high at 89.07 to the relationship between the Fiscal Dependence Levels of Economic Growth in Jambi indicates perfect correlation and positive direction.